2011
DOI: 10.1007/s11251-011-9171-8
|View full text |Cite
|
Sign up to set email alerts
|

Is the Study Process Questionnaire (SPQ) a good predictor of academic achievement? Examining the mediating role of achievement-related classroom behaviours

Abstract: Studies have shown that the Study Process Questionnaire (SPQ)-which provides a measure of student approaches to learning-is a relatively weak predictor of academic achievement. The present study sought to explore whether students' achievement-related classroom behaviours, as observed by teachers, can be used as a mediator between student approaches to learning and academic achievement. The SPQ was administered to 1,608 students enrolled in six different diploma programmes offered by a polytechnic in Singapore.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
1
21
1
3
Order By: Relevance
“…While empirical evidence on the use of learning strategies is inconsistent (e.g., Choy, O'Grady, & Rotgans, 2012;Dinsmore & Alexander, 2012), it is generally assumed that the use of deep-level learning strategies results in higher quality learning than the use of surface learning strategies (Gijbels, Van de Watering, Dochy, & Van den Bossche, 2005). However, dichotomizing surface learning strategies and deep-level learning strategies entails the danger of giving a too simplified description of strategy use as it suggests that learners are stable in their orientation (Dinsmore & Alexander, 2012).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…While empirical evidence on the use of learning strategies is inconsistent (e.g., Choy, O'Grady, & Rotgans, 2012;Dinsmore & Alexander, 2012), it is generally assumed that the use of deep-level learning strategies results in higher quality learning than the use of surface learning strategies (Gijbels, Van de Watering, Dochy, & Van den Bossche, 2005). However, dichotomizing surface learning strategies and deep-level learning strategies entails the danger of giving a too simplified description of strategy use as it suggests that learners are stable in their orientation (Dinsmore & Alexander, 2012).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…1, No. 1;December, 2017Rotgans (2012 found that the relationship between academic achievement and study processes is weak. Other researchers found that the goal of demonstrating high ability relative to others (ego motivation) was positively related to perceived value of surface-level strategies.…”
Section: Educational Motivation and Study Processesmentioning
confidence: 99%
“…The study of student approaches to learning (SAL) and problem-based learning (PBL) has been studied internationally (Gijbels et al 2009;Choy, O'Grady & Rotgans 2012). The research of SAL and PBL in Indonesia was conducted by Purwanto (2014) on the nursing students' approaches to learning in a problem-based learning (PBL) curriculum in Indonesia.…”
Section: Introductionmentioning
confidence: 99%